Shear characterisation of pultruded superstructural FRP-concrete push-outs. (February 2020) - Etim, Offiong; Gand, Alfred Kofi; Saidani, Messaoud; Fom, Pam; Ganjian, Eshmaiel; Okon, Eta
Abstract: In this paper, an investigation aimed at characterising the behaviour of headed shear studs in push-out testing is presented. The study aims to contribute to the limited knowledge of Pultruded Fibre Reinforced Polymer (PFRP)-concrete composites, highlighting the predominant failure mode and the underlying variables relevant for predictive analytical equations. Two phases of experimental push-out tests were carried out on composite slabs comprising of normal density concrete (NWC), and PFRP connected using steel headed studs. Phase one focused on studying the effects of headed shear stud configuration on the load capacity of the composite slabs, adopting 19 mm diameter studs. Phase two of the study was aimed at characterising the behaviour of the composite slab by varying the headed stud diameters. Two push-out test specimens adopted 12 mm diameter studs, and a third specimen within this phase adopted the 16 mm stud diameter. The dominant failure mode was bearing, net tension and shear out failures of the FRP plates. These modes of failure were distinctly different from those prevalent in the conventional steel-concrete composite, which is either stud shank failure or concrete pull out. The test investigation suggested a successive increase in shear capacity with increased stud sizes. Specimen with stud size of 16 mm attained higher shear strength per stud, approximately 29.4% in comparison to those with 12 mm diameter studs. The study observed that PFRP-concrete composites could mobilise between 40 and 50% shear resistances to that of their steel-concrete counterpart's. However, the intensity of bearing failure increases with increase in stud size, thereby compromising the ductility of shear connection.